Meningkatkan pemahaman peserta didik tentang dinasti abbasiyah dengan media pop up book - Mufidah, Zahrotul (Maliki Interdisciplinary Journal, 2025)
This study aims to enhance students’ understanding of the Abbasid Dynasty through the use of pop-up book learning media. Using the ADDIE development model, the media was designed with engaging and interactive three-dimensional elements. A trial involving 20 students showed a significant improvement in learning outcomes after using the media. Students also responded positively to the design and effectiveness in delivering the material. The pop-up book effectively addresses the limitations of conventional methods, making history learning more vivid, understandable, and enjoyable. Pop-up books can be used as an alternative learning medium in Islamic history education, significantly increasing student engagement and understanding. Going forward, it is recommended that this type of media be continuously adapted to student needs and characteristics to enhance meaningful learning.